Simulation and experimental investigation of a combined solar thermal and biomass heating system in Morocco. (December 2020) - Krarouch, Mohamed; Lamghari, Said; Hamdi, Hassan; Outzourhit, Abdelkader
Abstract: The integration of hybrid renewable energy systems, such as hybrid solar-biomass, to address thermal energy needs in various applications is a promising, efficient and eco-friendly solution that can be successfully applied for traditional baths in Morocco. Indeed, these systems are not widespread in Morocco, since traditional firewood furnaces are still commonly used for heating purposes in many different applications. Accordingly, the main objective of the study is to introduce a new hybrid solar-biomass system designed for space heating and hot water supply in a public bathhouse in Marrakesh, Morocco. This hybrid system includes small-scale pellet boilers and small dimension parabolic trough solar collectors (PTC), which is the first small-size PTC facility proposed for low temperature applications (less than 100 °C) in Morocco. Moreover, the preliminary simulation results of this hybrid solar-biomass system for space heating – case study – using TRNSYS software are presented. The use of such a hybrid system as a new design to retrofit conventional firewood boilers that are widely used for space and water heating in public bathhouses will lead to significant savings in firewood, which will contribute in particular to reducing deforestation in Morocco and will also result in substantial reductions in CO2 emissions.